Mobilizing Islam for National Populism in AKP's Turkey: Civilizationism in the Diyanet's Friday Sermons - Yakarlar, Tuğberk (Université d'Ottawa / University of Ottawa, 2024)
During the AKP (Justice and Development Party) era since 2002, Turkey visibly transformed from a secular country to a more Islamist-prone one, where the goal of raising "a pious generation" was declared as part of a top-down Islamization project. This thesis examines the mobilizing power of religion for populist appeals in politics as part of the government's religious nation-building project. The AKP's attempts at transforming the Turkish public space and politics along religious lines have been widely studied. However, the transformation of religious discourse in Turkey since the 2016 military coup attempt - thought to be led by the Gülen Movement, an influential Islamic order, and a former ally of the government - has been relatively less investigated. Based on a qualitative content analysis of the post-2016 Friday sermons issued by the Diyanet (the Directorate of Religious Affairs), the centralized government institution that runs the affairs of Sunni Islam in the country, this thesis provides an in-depth account of the AKP and President Erdoğan's expansionist politics, which underpin the use of religion in a way that aligns with their national-populist rhetoric and ideals. The findings suggest that in differentiation from the populist register that was found in Diyanet's Friday sermons, the Diyanet's rhetoric actively mobilizes "civilizationism", which frames the Turkish nation primarily as a religious community that spearheads the Muslim civilization, understood as a "geography of the heart", against its internal and external enemies. Beyond Turkey, the case of the Diyanet and its direct relation to civilizationism affirms the need to study populism as a phenomenon that embodies not only particular nationalisms, but also broader, civilizational worldviews.
Keywords: Populism; Nationalism; Religion; Civilizationism; Geography; Sociology of Religion; Political Sociology; Turkey; Diyanet